BRAND AUTHENTICITY AND CUSTOMER LOYALTY IN THE HOSPITALITY INDUSTRY IN EDO STATE, NIGERIA - Onovughakpor, Elizabeth; Peter Olannye, Ajulu (African Journal of Social and Behavioural Sciences, 2026)
This study investigates the relationship between components of brand authenticity and customer loyalty within the hospitality industry in Edo State, Nigeria. Adopting a cross- sectional survey research design, data were collected from a sample of 138 hotel customers selected from a population of 210 using the Taro Yamane formula and simple random sampling. A structured questionnaire was used to gather data measured on a five-point Likert scale. It was validated for content and face validity and tested for reliability using the test-retest method. Data were analyzed using descriptive statistics and multiple linear regression analysis. The findings revealed that brand message consistency (β = 0.165, p = 0.008), perceived customer value (β = 0.282, p = 0.000), brand transparency (β = 0.394, p = 0.000), and brand experience (β = 0.162, p = 0.040) all have significant positive effects on customer loyalty. The study concludes that brand authenticity is a critical driver of customer loyalty in the hospitality sector. It recommends that hotel operators should focus on consistent brand messaging, delivering customer value, enhancing transparency, and improving customer experiences to build lasting customer relationships and sustain competitive advantage.